Polycyclic aromatic hydrocarbon contamination in an urban area assessed by Quercus ilex leaves and soil - De Nicola, F; Alfani, a; Maisto, G (Environmental Science and Pollution Research, 2014)
We investigated the PAH contamination of Naples urban area, densely populated and with high traffic flow, by analyses of environmental matrices: soil and Quercus ilex leaves. Being some PAHs demonstrated to have hazardous effects on human health, the accumulation of carcinogenic and toxic PAHs (expressed as B(a)Peq) was evaluated in the leaves and soil. The main sources of the PAHs were discrim- inated by the diagnostic ratios in the two matrices. The urban area appeared heavily contaminated by PAHs, showing in soil and leaves total PAH concentrations also fivefold higher than those from the remote area. The soil mainly accumulated heavy PAHs, whereas leaves the lightest ones.Median values of carcinogenic PAH concentrations were higher in soil (440 ng g−1 d.w.) and leaves (340 ng g−1 d.w.) fromthe urban than the remote area (60 and 70 ng g−1 d.w., respectively, for soil and leaves). Also, median B(a)Peq concentrations were higher both in soil and leaves from the urban (137 and 63 ng g−1 d.w., respectively) than those from the remote area (19 and 49 ng g−1 d.w., respectively).Different from the soils, the diagnostic ratios found for the leaves discerned PAH sources in the remote and urban areas, highlighting a great contribution of vehicular traffic emission as main PAHsource in the urban area. Responsible
Keywords: carcinogenic pahs; Diagnostic ratios; Environmental matrices; Light and heavy PAHs; Naples urban area; PAH toxicity

A multi-approach monitoring of particulate matter, metals and PAHs in an urban street canyon - De Nicola, Flavia; Murena, Fabio; Costagliola, M. Antonietta; Alfani, Anna; Baldantoni, Daniela; Prati, M. Vittoria; Sessa, Ludovica; Spagnuolo, Valeria; Giordano, Simonetta (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
For the first time until now, the results from a prediction model (Atmospheric Dispersion Modelling System (ADMS)-Road) of pollutant dispersion in a street canyon were compared to the results obtained from biomonitors. In particular, the instrumental monitoring of particulate matter (PM10) and the biomonitoring of 14 polycyclic aromatic hydrocarbons (PAHs) and 11 metals by Quercus ilex leaves and Hypnum cupressiforme moss bags, acting as long- and short-term accumulators, respectively, were carried out. For both PAHs and metals, similar bioaccumulation trends were observed, with higher concentrations in biomonitors exposed at the leeward canyon side, affected by primary air vortex. The major pollutant accumulation at the leeward side was also predicted by the ADMS-Road model, on the basis of the prevailing wind direction that determines different exposure of the street canyon sides to pollutants emitted by vehicular traffic. A clear vertical (3, 6 and 9 m) distribution gradient of pollutants was not observed, so that both the model and biomonitoring results suggested that local air turbulences in the street canyon could contribute to uniform pollutant distribution at different heights.
The following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Holm oak leaves; metals; Moss bags; Naples urban area; PAHs; Pollutant dispersion model